Climate-induced small pelagic fish blooms in an overexploited marine ecosystem of the South China Sea. (December 2022) - Zhang, Kui; Li, Miao; Li, Jiajun; Sun, Mingshuai; Xu, Youwei; Cai, Yancong; Chen, Zuozhi; Qiu, Yongsong
Graphical abstract: Highlights: Small pelagic fish blooms in Beibu Gulf occurred in summers of La Niña years. Japanese jack mackerel and Japanese scad contributed to the blooms. Higher densities, smaller body sizes, and later spawning times followed La Niña events. The blooms affected abundance, diversity, and spatial pattern of the fish community. Abstract: Marine ecosystems are a primary conservation concern because of the separate and synergistic effects of overfishing and climate change on their productivity and biodiversity. For the purpose of implementing ecosystem-based fisheries management, it is essential to understand how fish stocks respond to climate change in marine ecosystems, especially those that have been overexploited. The Beibu Gulf in the northwestern part of the South China Sea has long been one of China's major fishing grounds. After the collapse of the demersal ecosystem in 1990 s, small pelagic fishes, including Japanese jack mackerel ( Trachurus japonicus ) and Japanese scad ( Decapterus maruadsi ), have occupied a more-important ecological niche in this gulf. However, insufficient research on how small pelagic fish respond to climate change creates great uncertainty for implementing the current management measures. This study used fish data of trawl surveys and environmental data to investigate possible mechanisms leading to dramatic fluctuations in small pelagic fish populations and their possible effects on the Beibu Gulf marine ecosystem. Abnormal blooms of small pelagic fish, especially T. japonicus and D. maruadsi, occurred following four La Niña events (in 2007/2008, 2010/2011, 2011/2012, and 2020/2021). Moreover, the dominant fish species shifted observably and regularly, Shannon–Wiener diversity and Pielou's evenness decreased significantly in the northeastern coastal waters of the gulf, and the spatial pattern of the fish community was reorganized in this ecosystem. The small pelagic fish blooms in summers probably resulted from a combination of climate change, overfishing, and a summer fishing moratorium, which thereby caused a series of responses in the marine ecosystem. Fluctuations in the small pelagic fish populations after La Niña events seemed more dramatic after the collapse of demersal fish stocks. Therefore, we emphasize the need for implementing ecosystem-based, preventive, and adaptive fisheries management.